The influence of climate change advisory bodies on political debates: evidence from the UK Committee on Climate Change. (21st October 2021) - Averchenkova, Alina; Fankhauser, Sam; Finnegan, Jared J.
ABSTRACT: Climate change advisory bodies are rapidly proliferating around the world, often with statutory underpinning. While they are argued to be an important component of effective climate governance, few studies have systematically assessed their political influence. Using the UK Committee on Climate Change (CCC) as a case, this paper investigates how such bodies influence political debates on climate change. To do so, we build an original dataset of all CCC mentions in UK Parliamentary proceedings from 2008–2018. We find that CCC analysis is used by all major political parties, that its influence has grown over time and that it has influenced policy debates both within its statutory remit (carbon budgets) and more broadly (energy policy and flood defence spending). Furthermore, most politicians have been supportive of the CCC. They have utilized the information it produces to hold government accountable and to argue for more ambitious policy. We find little evidence that CCC analysis is politicized or that it merely functions as a 'legitimiser', providing justification for the government's pre-decided policy choices. Instead, we find that the CCC functions primarily as a knowledge broker, offering trusted information to policymakers, and at times as a policy entrepreneur. Overall, the CCC experience demonstrates that climate change advisory bodies can play a key role in climate governance. Key policy insights The information and analysis produced by the CCC is widely cited by Parliamentarians across the political spectrum and is often used as the technical basis for political arguments calling for greater ambition. CCC evidence has substantial influence in areas that are directly covered by its core statutory mandate, but also wider climate change-related Parliamentary debates, indicating knowledge spillovers. The UK experience shows that an expert advisory body can strengthen climate governance by serving as an impartial knowledge broker, contributing to more evidence-based and ambitious policymaking.